Pemikiran Politik al-Shawkânî dalam Fath al-Qadîr - Hanafi, Yusuf (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2014)
Muhammad b. ‘Alî Muhammad b. ‘Abd Allâh al-Shawkânî al-San‘ânî. He was born in the Hijrah in Shawkân village, Yemen on Monday 28 Dhû al-Qa‘dah 1172 H and died on Tuesday, 27 Jumâd al-Akhîr 1250 H at the age about 78 years. Al-Shawkânî grew up in the San‘a city, it is the capital of the republic of Yemen now. He study first time about religion from his father, then from renowed scholars in San‘a and its surrounding, he was known as a scolar who mastered the various branches of religious sciences. Such as tafsîr, h}adîth, fiqh, us}ûl al-fiqh, history, science of kalâm, philosophy, balâghah, mant}iq etc. the main issue in this article is how political thought in the book of tafsir Fath al-Qadîr is the work of Shawkânî. At the end of article, the authors found that the intended political thinking in the study of Fath al-Qadîr is about constitutional ideas. These ideas about the constitution is limited to the concept of leadership and deliberation, the concept of the right of citizen to obtain justice, and the concept pf the right of citizens to live association and assembly